Ex vivo expansion of human Tregs specific for alloantigens presented directly or indirectly - Veerapathran, Anandharaman (American Society of Hematology, 2011)
Adoptive transfer of regulatory T cells (Tregs) prevents GVHD in experimental animals. Because antigen activation drives Treg function, we measured the frequency, growth requirements, and function of alloantigen-specific (allospecific) Tregs from human blood. When alloantigen was presented directly, the precursor frequency of allo-specific Tregs in normal individuals was 1.02% (95% confidence interval [95% CI]: 0.65-1.59) and non-Tregs 1.56% (95% CI: 0.94-2.55). When alloantigen was presented indirectly, the frequency of specific Tregs was approximately 100-fold less. Purified Tregs were expanded with APCs, rapamycin, IL-2, and IL-15. In 12 days, allo-specific Tregs expanded 793-fold (95% CI: 480-1107), with duplication approximately every 24 hours. Purified allo-specific Tregs suppressed responses to specific alloantigen selectively and were approximately 100-fold more potent than polyspecific Tregs and nonexpanded Tregs. Allo-specific Tregs maintained high expression of Foxp3, Bcl-2, lymphoid homing receptor CD62L, and chemokine receptor CCR7, predicting sustained function and migration to lymphoid tissues in vivo. Allo-specific Tregs produced TGF-β and IL-10 and expressed more cytoplasmic CTLA-4 compared with non-Tregs. These data provide a platform for the selective expansion of Tregs against major and possibly minor histocompatibility antigens and predict the feasibility of adoptive immunotherapy trials using Tregs with indirect allo-recognition for preventing GVHD while sparing GVL effects.